2009
DOI: 10.1111/j.1600-079x.2008.00656.x
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the neuroprotective effects of melatonin in an in vitro experimental model of age‐induced neuronal apoptosis

Abstract: The neuroprotective effects of melatonin in an experimental model of aging-induced apoptosis have been examined. Cerebellar granule neurons show characteristics of apoptosis after 17 days in culture (DV). The addition of melatonin to neuronal cell cultures (100-500 mum) resulted in neuroprotective and antiapoptotic effects, which were revealed by nuclear condensed cell counting. In a thorough analysis by Western-blot of the potential pathways responsible for melatonin's neuroprotective effects, we found an inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 47 publications
0
27
1
Order By: Relevance
“…An alternative explanation is that mitochondrial ROS exert a direct effect on the signaling pathway leading to hyperphosphorylation of tau. For example, the glycogen synthase kinase 3 beta (GSK-3β), one of the major kinases modulating tau phosphorylation has been shown to be inhibited by antioxidant treatment [53], indicating that ROS activate the enzyme and result in increased phosphorylation of tau. Further experiments are required to clarify whether ROS affect tau phosphorylation directly or via their effect on blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative explanation is that mitochondrial ROS exert a direct effect on the signaling pathway leading to hyperphosphorylation of tau. For example, the glycogen synthase kinase 3 beta (GSK-3β), one of the major kinases modulating tau phosphorylation has been shown to be inhibited by antioxidant treatment [53], indicating that ROS activate the enzyme and result in increased phosphorylation of tau. Further experiments are required to clarify whether ROS affect tau phosphorylation directly or via their effect on blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…Our recent study showed that melatonin restored the impaired memory and attenuated the alteration of the amyloid precursor protein (APP) proteolytic processing enzyme (α- and β-secretases) expression in the hippocampus of aged mice (Mukda et al, 2016[40]). Melatonin preserved the relative protein levels of SIRT1 in the senescence-accelerated mice (SAMP8) (Cristofol et al, 2012[14]; Gutierrez-Cuesta et al, 2008[23]; Tajes Orduna et al, 2009[55]) and in the hippocampus of total sleep-deprived rats (Chang et al, 2009[12]). Age-related neuronal energy deficits contribute to the pathogenesis of several neurodegenerative disorders, such as Alzheimer's disease.…”
Section: Introductionmentioning
confidence: 99%
“…Melatonin ( N ‐acetyl‐5‐methoxytryptamine) is a hormone produced mainly by the pineal gland and which has a wide spectrum of biological effects. Melatonin not only participates in the regulation of the circadian rhythms but may also exerts neuroprotective effect in neurodegenerative disorders [19–21]. The protective effect of melatonin is, in part, mediated by mitochondria [22].…”
Section: Introductionmentioning
confidence: 99%